Endometrial ILKAP expression among patients with endometriosis and its association with clinical characteristics. Issue 1 (July 2015) - Shao, Guangying; Zheng, Qiaomei; Xu, Xiaoxuan; Zhao, Jing; Liu, Peishu
Abstract: Objective: To investigate expression of ILKAP among women with endometriosis and its association with clinical characteristics. Methods: A retrospective study was conducted at a center in China in 2012, using samples of ectopic (n = 55) and eutopic (n = 33) endometrium from women with endometriosis, and control endometrium samples (n = 33) from women without endometriosis. Information on clinical characteristics was obtained from records. The expression of ILKAP was tested by immunohistochemistry. Results: The expression of ILKAP was higher in the secretory phase of the menstrual cycle than in the proliferative phase, and it was lower in eutopic and ectopic endometriosis tissue than in control endometrium ( P  < 0.001 for both). A lower expression of ILKAP in ectopic endometrium was associated with moderate-to-severe dysmenorrhea, infertility for more than 1 year, a cancer antigen 125 level of more than 35 U/mL, a disease duration of at least 1 year, and American Fertility Society grade IV disease ( P  < 0.05 for all). Conclusion: A low level of ILKAP could facilitate the pathogenesis of endometriosis. Additionally, the level of ILKAP expression in ectopic endometrium might reflect the severity of endometriosis.